Pengaplikasian Panel Surya dan Automatic Transfer Switch (ATS) untuk Menggerakkan Pompa Tanaman Hidroponik sebagai Sumber Energi Terbarukan - Kurniawan, Muhammad Ridwan; Abadi, Zainal (Lembaga Yasin AlSys, 2024)
Solar panels are renewable energy which is very useful for agricultural needs to meet electricity needs, one of which is its application in agriculture, namely as a pump driver for hydroponic plants. Hydroponics is farming with an emphasis on meeting the nutritional needs of plants using water as a medium with a nutrient solution as fertilizer. In the hydroponic system the pump must be on continuously, for this reason the Automatic Transfer Switch (ATS) tool is used to substitute the electrical energy of the State Electricity Company (PLN) with the electrical energy of solar panels in the event of a power outage from the State Electricity Company (PLN) which aims to drain nutrient water. This research aims to apply solar panels to a hydroponic plant system and apply the Automatic Transfer Switch (ATS) tool as a substitute for the State Electric Company's (PLN) electrical energy and solar panels. This research was carried out on Jalan Polonia no.11 fresh water east, North Padang District, Padang City, West Sumatra in January – March 2024, with the initial stages (1) preparation, (2) solar panel assembly, (3) analysis of test results , (4) preparation of reports. The results of this research can determine the power output required by solar panels as a renewable energy source as well as the application of the Automatic Transfer Switch (ATS) in hydroponic plant cultivation.